THE ACTIVITIES OF TIMURIAN PRINCESSES ON THE BRIGHT PAGES OF OUR HISTORY (Conferencea, 2024)
The article provides information about the lives of enlightened, wise, talented poetesses and scholars among the women of the Timurid dynasty, one of the most powerful centralized dynasties of the Middle Ages.